2019
DOI: 10.1111/1346-8138.15193
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy of apremilast and biologics in patients with psoriasis showing biologic fatigue

Abstract: Biologics have been shown to constitute a highly effective treatment for patients with psoriasis. However, a significant number of patients treated with biologics will discontinue them due to loss of efficacy over time, a phenomenon known as biologic fatigue or secondary failure. Combination therapy of biologics with other agents can be considered as a treatment option in such cases. Information regarding the efficacy and safety of adding apremilast to biologic therapy in patients with psoriasis is limited. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…methotrexate) obtained PASI50-100 throughout a follow up period of 3-9 months with similar treatment-emergent adverse effects [TEAE] to monotherapy (Table1). 13,[19][20][21][22][23][24][25][26][27][28][29][30][31] Collectively several case studies have noted that the addition of apremilast to either systemic biologic or nonbiologic therapies had a mean additional improvement in PASI scores between 31.8-77.4% for patients that were either unsatisfied with their current regimen or experienced secondary failure. 13,19,21,22 While additional efficacy varied depending on the pre-apremilast regimen, most patients saw durable results with a range of means between 12 and 31 weeks.…”
Section: Combination Therapy For Psoriasis and Psoriatic Arthritismentioning
confidence: 99%
See 4 more Smart Citations
“…methotrexate) obtained PASI50-100 throughout a follow up period of 3-9 months with similar treatment-emergent adverse effects [TEAE] to monotherapy (Table1). 13,[19][20][21][22][23][24][25][26][27][28][29][30][31] Collectively several case studies have noted that the addition of apremilast to either systemic biologic or nonbiologic therapies had a mean additional improvement in PASI scores between 31.8-77.4% for patients that were either unsatisfied with their current regimen or experienced secondary failure. 13,19,21,22 While additional efficacy varied depending on the pre-apremilast regimen, most patients saw durable results with a range of means between 12 and 31 weeks.…”
Section: Combination Therapy For Psoriasis and Psoriatic Arthritismentioning
confidence: 99%
“…13,[19][20][21][22][23][24][25][26][27][28][29][30][31] Collectively several case studies have noted that the addition of apremilast to either systemic biologic or nonbiologic therapies had a mean additional improvement in PASI scores between 31.8-77.4% for patients that were either unsatisfied with their current regimen or experienced secondary failure. 13,19,21,22 While additional efficacy varied depending on the pre-apremilast regimen, most patients saw durable results with a range of means between 12 and 31 weeks. 13,[19][20][21][22][23][24][25] Several studies also found additional benefit in combining narrow-band UVB (nbUVB) phototherapy with apremilast, with additional improvements in PASI of 76.4-81.5%.…”
Section: Combination Therapy For Psoriasis and Psoriatic Arthritismentioning
confidence: 99%
See 3 more Smart Citations